Systematic Literature Review terhadap Klasifikasi Emosi pada Lirik Lagu Berbahasa Ambon menggunakan Metode Bidirectional LSTM dengan Glove Word Representation Weighting - Kholida Zia Abidin; Arief Setyanto; Rudyanto Arief (UNIVERSITAS STEKOM, 2023)
One form of text that can express emotions is lyrics. Lyrics are a type of literary work expressed in the form of words, the contents of which can express the songwriter's personal feelings, thoughts, and emotions. Therefore, the lyrics can be used as an object of research on the classification of emotions. The classification of song lyrics really requires bi-LSTM to be the input value when classifying data in the form of song lyrics in order to get high accuracy results. This research was carried out systematically and the results were measurable. Descriptive qualitative research was used in this research. The results of identification based on case studies and statistics show that the reviews of popular topics are identical. The classification of song lyrics really requires bi-LSTM to be the input value when classifying data in the form of song lyrics in order to get high accuracy results.